CORPORATE SOCIAL RESPONSIBILITY TERHADAP LOYALITAS NASABAH YANG DIMEDIASI OLEH CITRA PERUSAHAAN - Ni Nyoman Kerti Yasa; Putu Gde Sukaatmadja; I G.N. Jaya A. Widagda; I Putu Andika Angga Putra (Jurnal Keuangan dan Perbankan, 2015)
The purpose of this study was to determine the effect of corporate social responsibility towards the customerloyalty, mediated by corporate image. The population in this study was the customers of BPR. The number ofsamples was 120 respondents by using purposive sampling method. The data analysis technique used was thetechnique of path analysis and the Sobel test. The results of this study indicated that CSR had a positive andsignificant impact on the corporate image and the customer loyalty of BPR in Denpasar. The variable ofcorporate image was proved to be able to mediate the effects of CSR on BPR customer loyalty in Denpasarsignificantly. The implication of this research was suggested to BPR industry in Denpasar to implement andto communicate the CSR activities done to increase the corporate image and to increase the customer loyalty.